PENINGKATAN PANGSA PASAR PADA PERUSAHAAN SMARTPHONE MELALUI BRAND LOYALTY - NURUL FADHILA, AMELIA; NUNO SUTRISNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research aims to determine the effect of Brand Experience to Brand Loyalty Smartphone in Bekasi through Brand Satisfaction and Brand Trust. The research design used is causality research. Where each variable are measured with 5 points Likert Scale. Primary data for this research were gathered by questionnaire. Purposive Sampling was used in this study, with 260 respondents. WarpPLS SEM 7.0 is the tool use for processing of research data. The results of this research show that Brand Experience have an influence of Brand Loyalty through Brand Satisfaction and Brand Trust. This research will offer insights and recommendations to smartphone companies, particularly Apple.Inc with iPhone product which is the object of this research, is capable of gaining market share in Indonesia’s smartphone sector.